Effect of Social Comparison in Social Media on Psychological Distress in Adolescents: Role of Emotion Regulation as Moderator - Tedjawidjaja, Detricia; Christanti, Dessi (Journal of Educational, Health and Community Psychology, 2022)
Access to social media can encourage adolescents to make social comparisons, causing psychological distress. There are two emotion regulation strategies, namely cognitive reappraisal and expressive suppression. The cognitive reappraisal strategy weakens the relationship between social comparison on social media and psychological distress, while the expressive suppression strategy strengthens it. This study aimed to examine the role of emotion regulation as the moderating variable between social comparison and psychological distress.